Diabetic foot ulcer healing with polylactic acid membrane assessed by thermographic imaging: a case report - Víctor Manuel Loza-González; Mario Aurelio Martínez-Jiménez; Ana Lorena Novoa-Moreno; José Luis Ramírez-GarcíaLuna; José Luis Ramírez-GarcíaLuna; Alejandra Ortiz-Dosal; Alejandra Ortiz-Dosal; Eleazar Samuel Kolosovas-Machuca; Eleazar Samuel Kolosovas-Machuca (Frontiers in Medicine)
Diabetic foot ulcers reduce patient’s quality of life and increase treatment costs, evaluating this condition is promising. We report the clinical progression of an elderly patient who developed a diabetic foot ulcer following minor trauma. She was treated for over 2 months until her condition progressed to Grade 4 on the Wagner Classification of Diabetic Foot. A Serial infrared thermography was performed. The treatment plan included antibiotics and a polylactic acid membrane until complete ulcer remission. Thermographic imaging showed a quantitative reduction of the temperature differences between the affected and contralateral foot from an initial ΔT: −4.6°C ± 2.4, progressing to ΔT: −1.7°C ± 1.6 at 12 weeks, and a temperature reduction from the proximal third tibial area with ΔT: −1.7°C ± 0.6, with a change to ΔT 0.8°C ± 0.4 at 12 weeks near the metatarsal bone region. This article underscores the use of infrared thermography to give physicians feedback on ulcer healing progression phases and treatment effectiveness.